Predicting Vapor-Phase Concentrations for the Assessment of the Odor Perception of Fragrance Chemicals Diluted in Mineral Oil - Patrícia Costa (2017)
In this study, the Henrys law methodology is applied to predict the release of odorants present in single and multicomponent fragrance mixtures diluted in mineral oil, a simplified matrix used in cosmetic products. To attain this goal, the experimental Henrys law constant (H) of each odorant in each studied fragrance system (containing one, two, three, or four odorants) was first evaluated by plotting their liquid phase and experimental vapor phase concentrations assessed by headspace gas chromatography. From that point, the H value of each odorant in the multicomponent fragrance system was predicted from its corresponding Hexp in the single fragrance component system. The theoretical vapor-phase concentrations were also calculated using the activity coefficients for vaporliquid equilibria by applying the thermodynamic UNIFAC model. The odor intensity and character of the studied fragrance systems were assessed through the Stevenss power law and Strongest Component models (psychophysical models). This study confirmed that the headspace concentrations and odor intensity of each odorant present in a multicomponent fragrance mixture dissolved in mineral oil can be efficiently predicted from its corresponding H determined when present alone in the simplified matrix, for low concentrations. Also, comparing both methodologies, UNIFAC and Henrys law, it was concluded that Henrys law is a better predictive model for the vaporliquid equilibria, showing lower deviations from the experimental data. Therefore, the proposed predictive mathematical model can be attractive for the assessment of sensory quality of multicomponent fragrance systems in early formulation stages.